Physical properties and biological impact of 90Y microspheres prepared by sol-gel method for liver radioembolization. (January 2023) - Maciak, Maciej; Konior, Marcin; Wawszczak, Danuta; Majewska, Aleksandra; Brodaczewska, Klaudia; Piasecki, Piotr; Narloch, Jerzy; Sady, Maria; Olszewski, Jarosław; Gajewski, Zdzisław; Kieda, Claudine; Dziel, Tomasz; et al.
Abstract: Microspheres for liver radioembolization for human use have high requirements in terms of their toxicity and biocompatibility on the one hand, but also typical properties such as physical and chemical durability or specific activity on the other hand. Developed manufacturing process based on the sol-gel method allowed to obtain spherical, yttrium trioxide grains of fully polycrystalline structure with diameters between 20 μm and 100 μm. The work is focused on a further investigation concerning the Y2 O3 microspheres including physical, radiometric, dosimetric, and biological experiments. Neutron activation analysis confirmed a high concentration of radioactive 90 Y in the sample. The developed procedure for determining the specific activity of a single microsphere showed that at the time of administration, the activity can be specified at the level of 2600–3200 Bq per microsphere. FLUKA Monte Carlo code was used to prepare model for the calculation of dose distributions at the microscopic level, indicating that locally occurring heterogeneities can lead to cold spots during radioembolization. The data obtained from the simulation enabled analysis of the absorbed dose delivered by gel 90 Y2 O3 microspheres as a function of radioactivity concentration, initial specific activity, or microsphere concentration in the sample. The reduction in colorectal cancer cell proliferation in vitro confirms the significant influence of beta ray radiation from yttrium-90 trioxide microspheres. Histopathological examination of the distribution of microspheres in the porcine model confirmed the proper location of yttrium trioxide microspheres inside blood vessels in a porcine model. Gel Y2 O3 microspheres manufactured using the sol-gel method showed relevant properties, indicating the possible use of microspheres for further biological and preclinical studies. Highlights: Gel Y2 O3 microspheres were manufactured using developed sol-gel method. Specific activity was specified as 2500–3200 Bq per microsphere. HCT116 cell proliferation was reduced in in-vitro experiment with Y2 O3 microspheres. Histopathological examination proved proper location of the microspheres in tissue. Monte Carlo-based model allowed to analyse the spatial distribution of microspheres.